PUBLIC ADMINISTRATION IN TERMS OF STATE-PRIVATE PARTNERSHIP - Kruglov V.V. (Pressing Problems of Public Administration, 2015)
The article reviews the main approaches to the notion of public administration. An analysisof functions of the state authority and local bodies that perform public administration whenimplementing state-private partnership projects has been carried out. The peculiarities offunctions of public administration in terms of state-private partnership have been determined.